Incidence And Management Of Tumors In Domestic Animals - Dhami , Mehul A.; Kelawala, N.H. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A total of 33 cases(25 canine, 3 bovine, 3 equine and 2 camel) of tumors were attended and managed surgically in different species of domestic animals over a period of six months. Canine tumours mainly included the mammary gland tumors of benign or malignant nature and of single or multiple type. The clinical diagnosis based on gross appearance of tumorous growths was made followed by surgical resection using standard anesthetic and operative techniques. No any untoward sequelae was noted in any of the cases attended. Surgical removal of the entire mass was the treatment of choice. Benign tumors only affected the site but most malignant cancers had already spread before being diagnosed and treated. It was inferred that canines are more prone to tumors of varying nature and mammary tumors in particular, which can be successfully managed surgically.
Keywords: Domestic animals; Tumurs; Incidence; Surgical management